Gregor and the Code of Claw - Collins, Suzanne (New York : Scholastic Press, 2007)
When twelve-year-old Gregor finally learns the ancient prophecy, which foretells his death, he must gather his courage to defend Regalia from the army of rats, take his mother and sister home safely, and fight his own dark side.
Keywords: Brothers and sisters -- Fiction; Animals -- Fiction; Fantasy